CONTEMPORARY STATE AND DESTINATIONS OF SCIENTIFIC RESEARCH OF THE INSTITUALIZATION OF THE INTERACTION OF PUBLIC AUTHORITIES WITH THE PUBLIC - Dashkova , K. S. (Theory and Practice of Public Administration, 2021)
The article considers the state of the state management scientific development of the problems of the institutional maintenance of the interaction of public authorities with the public and the definition of the unsearched aspects and prospective destinations of the scientific research in this area. There was also analyzed the relevance of the research of the issues of the institualization of the relationships of public authorities and the public as the necessary condition to develop a democratic state and observe the rights and freedoms of citizens when they participate in the process of the management decisions making. There were also systematized the newest publications on the important issues of the public authorities functioning as the mechanism of the state regulation of social institutions and the means of the public social interests realization.The conclusion was made that the research of the institualization of the interaction of the public authorities with the public is of immediate interest in the scientific thought. The analysis of the thesis papers on this topic witnesses the fragmentary nature of its development, the absence of any reliable theoretical and legal rules and regulations necessary to solve the range of problems on providing the interaction of citizens with authorities, the stimulation of the political activity of the citizens, the development of the civil society. During the last years, there has been activated the research of the state and the public interaction in different areas of public management, the forms, and functions of which are conditioned with the special terms of the area. At the same time, there is a range of areas where this interaction is not researched enough, in particular, the law enforcement, the judicial power, and these issues should become a subject of further scientific search.